Social Innovation: opportunity for business sustainability - Araque Geney, Erika Astrid; Álvarez Contreras, Diana Esther (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Faced with unresolved social, economic and environmental problems, it is common to observe the performance of companies in the search for alternative solutions. Social innovation has become a tool to generate growth, consolidation and success in organizations. This type of innovation includes changes at the managerial, organizational and human level, in the face of changes in services and products, as well as in the processes offered by technological innovation. The purpose of this article is to present a documentary review of social innovation; in addition to the management of innovation in companies and finally, it addresses the issue of social innovation from the approach of business sustainability, as a strategy that allows companies to become sustainable, innovate and ensure that their operations and results do not have a negative impact on society and the environment.